Isolation and Taxonomic Characterization of Novel Haloarchaeal Isolates From Indian Solar Saltern: A Brief Review on Distribution of Bacteriorhodopsins and V-Type ATPases in Haloarchaea - Verma, Dipesh Kumar; Chaudhary, Chetna; Singh, Latika; Sidhu, Chandni; Siddhardha, Busi; Prasad, Senthil E.; Thakur, Krishan Gopal (Frontiers in Microbiology, 2020)
Haloarchaea inhabit high salinity environments worldwide. They are a potentially rich source of crucial biomolecules like carotenoids and industrially useful proteins. However, diversity in haloarchaea present in Indian high salinity environments is poorly studied. In the present study, we isolated twelve haloarchaeal strains from hypersaline Kottakuppam, Tamil Nadu solar saltern in India. 16S rRNA based taxonomic characterization of these isolates suggested that nine of them are novel strains that belong to genera Haloarcula, Halomicrobium, and Haloferax. Transmission electron microscopy suggests the polymorphic nature of these haloarchaeal isolates. Most of the haloarchaeal species are known to be high producers of carotenoids. We were able to isolate carotenoids from all these twelve isolates. The UV-Vis spectroscopy-based analysis suggests that bacterioruberin and lycopene are the major carotenoids produced by these isolates. Based on the visual inspection of the purified carotenoids, the isolates were classified into two broad categories i.e., yellow and orange, attributed to the differences in the ratio of bacterioruberin and lycopene as confirmed by the UV-Vis spectral analysis. Using a PCR-based screening assay, we were able to detect the presence of the bacteriorhodopsin gene (bop) in eleven isolates. We performed whole-genome sequencing for three bop positive and one bop negative haloarchaeal isolates. Whole-genome sequencing, followed by pan-genome analysis identified multiple unique genes involved in various biological functions. We also successfully cloned, expressed, and purified functional recombinant bacteriorhodopsin (BR) from one of the isolates using Escherichia coli as an expression host. BR has light-driven proton pumping activity resulting in the proton gradient across the membrane, which is utilized by V-Type ATPases to produce ATP. We analyzed the distribution of bop and other accessory genes involved in functional BR expression and ATP synthesis in all the representative haloarchaeal species. Our bioinformatics-based analysis of all the sequenced members of genus Haloarcula suggests that bop, if present, is usually inserted between the genes coding for B and D subunits of the V-type ATPases operon. This study provides new insights into the genomic variations in haloarchaea and reports expression of new BR variant having good expression in functional form in E. coli.